2020
DOI: 10.1109/tse.2018.2870895
|View full text |Cite
|
Sign up to set email alerts
|

Finding Faster Configurations Using FLASH

Abstract: Finding good configurations of a software system is often challenging since the number of configuration options can be large. Software engineers often make poor choices about configuration or, even worse, they usually use a sub-optimal configuration in production, which leads to inadequate performance. To assist engineers in finding the better configuration, this article introduces FLASH, a sequential model-based method that sequentially explores the configuration space by reflecting on the configurations eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
193
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(195 citation statements)
references
References 46 publications
(79 reference statements)
1
193
1
Order By: Relevance
“…A typical approach uses sensitivity analysis [29], where performance models are learned by measuring the performance of the system under a limited number of sampled configurations. While this approach is cheaper and more effective than manual exploration, it still incurs the expense of extensive data collection about the software [3], [4], [7], [8], [10], [12], [26], [27], [30]. This is undesirable since this data collection has to be repeated if ever the software is updated or the environment of the system changes abruptly.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…A typical approach uses sensitivity analysis [29], where performance models are learned by measuring the performance of the system under a limited number of sampled configurations. While this approach is cheaper and more effective than manual exploration, it still incurs the expense of extensive data collection about the software [3], [4], [7], [8], [10], [12], [26], [27], [30]. This is undesirable since this data collection has to be repeated if ever the software is updated or the environment of the system changes abruptly.…”
Section: Motivationmentioning
confidence: 99%
“…It has recently been shown that exact measures like MMRE can be somewhat misleading to assess configurations [12], [27], [36].…”
Section: Evaluation Criterionmentioning
confidence: 99%
See 3 more Smart Citations